2022
DOI: 10.1093/ejcts/ezac575
|View full text |Cite
|
Sign up to set email alerts
|

Tumour location predicts occult N1 nodal metastasis in clinical stage I non-small-cell lung cancer

Abstract: Objectives Pathological lymph node metastases are often observed in patients with clinical N0 lung cancer. Identifying preoperative predictors of occult hilar nodal metastasis is important in determining the surgical procedure in patients with clinical stage I non-small cell lung cancer. This study aimed to determine the frequency and predictors of occult hilar nodal metastasis by tumour location in these patients. Methods Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
5
6
0
Order By: Relevance
“…19 In 2022, we published a study in the Journal of Translational Lung Cancer Research on the factors influencing the measurement accuracy of this method in each lung lobe and pointed out that the depth ratio method could accurately distinguish the inner, middle, and outer band ranges in three-dimensional space and eliminate the interference of mediastinal structures, to the greatest extent, in the three symmetrical partitions of the bilateral lungs. 20 The present study found a significant correlation between the probability of lymph node metastasis and the tumor's location within the inner (depth ratio >66.7%) zones, which aligns with the findings of Kawamoto et al 9 Conversely, Tane et al 21 did not observe a significant difference in the rate of lymph node metastasis between internal and external lesions. Additionally, DuComb et al 22 analyzed the NLST database to investigate the relationship between the coordinate position of solid nodules measuring 8-30 mm and N2/N3 lymph node metastasis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…19 In 2022, we published a study in the Journal of Translational Lung Cancer Research on the factors influencing the measurement accuracy of this method in each lung lobe and pointed out that the depth ratio method could accurately distinguish the inner, middle, and outer band ranges in three-dimensional space and eliminate the interference of mediastinal structures, to the greatest extent, in the three symmetrical partitions of the bilateral lungs. 20 The present study found a significant correlation between the probability of lymph node metastasis and the tumor's location within the inner (depth ratio >66.7%) zones, which aligns with the findings of Kawamoto et al 9 Conversely, Tane et al 21 did not observe a significant difference in the rate of lymph node metastasis between internal and external lesions. Additionally, DuComb et al 22 analyzed the NLST database to investigate the relationship between the coordinate position of solid nodules measuring 8-30 mm and N2/N3 lymph node metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…This study identified depth ratio as an independent risk factor for the development of lymph node metastasis in T1 lung adenocarcinoma. Studies have reported a correlation between the location of the tumor center and lymph node metastasis; the closer the tumor is to the center, the higher the risk of lymph node metastasis 9,17 . Our study yielded similar results.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations